2 Cases of Bullosis Diabeticorum following Long-Distance Journeys by Road: A Report of 2 Cases. (16th October 2012) - Bello, Fatima; Samaila, O. Modupe; Lawal, Yakubu; Nkoro, U. Kufre
Abstract : Background . Bullosis diabeticorum is a distinct, spontaneous, noninflammatory, and blistering condition of acral skin that is unique to diabetics. It is rare. Exact aetiopathogenesis is not known, but many attributed peripheral neuropathy as a potent risk factor, others hypothesized the role of trauma, UV light, and nephropathy. Aim . To present cases of bullosis diabeticorum following long-distance journeys by road. Methods . History and physical examinations were done on 2 diabetics who presented with bilateral feet bullae following a long journey. Biopsy of a circumferential area of the bullae including adjoining apparently normal skin was done. Results . Features of peripheral neuropathy were noted. One developed digital gangrene without features of peripheral vascular disease. Culture of aspirate from a bullae yielded Staphylococcus aureus . Tissue biopsy showed hyperkeratotic focally acanthotic pigmented epidermis with subcorneal separation of the granular layer of the epidermis by aggregates of viable and nonviable polymorphs and lymphocytes. There is mild acantholysis of the epidermis, and a fibrocollagenous dermis which is moderately infiltrated by lymphocytes. Conclusion . Long journeys by road is a strong factor in the aetiopathogenesis of bullosis diabeticorum on a background of peripheral neuropathy. Diabetics especially those with peripheral neuropathy should be cautious while traveling long journeys by road.